The Use of Botulinum Toxin in Complex Hernia Surgery: Achieving a Sense of Closure - Whitehead-Clarke, Thomas; Windsor, Alastair (Frontiers in Surgery, 2021)
Abdominal wall surgeons have developed a host of tools to help facilitate fascial closure. Botulinum toxin A is one of the most recently identified treatments and has grown in popularity over recent years; showing great promise in a number of case series and cohort studies. The toxin paralyses lateral abdominal wall muscles in order to increase laxity of the tissues—facilitating medialisation of the rectus muscles. Several research groups around the world are developing expertise with its use-uncovering its potential. We present a review of the relevant literature over the last two decades, summarising the key evidence behind its indications, dosing and effects.